Management of low back pain in Australian emergency departments. Issue 10 (4th June 2019) - Ferreira, Giovanni E; Machado, Gustavo C; Abdel Shaheed, Christina; Lin, Chung-Wei Christine; Needs, Chris; Edwards, James; Facer, Rochelle; Rogan, Eileen; Richards, Bethan; Maher, Christopher G
Abstract : Background: To describe the diagnoses of people who present to the emergency department (ED) with low back pain (LBP), the proportion of people with a lumbar spine condition who arrived by ambulance, received imaging, opioids and were admitted to hospital; and to explore factors associated with these four outcomes. Methods: In this retrospective study, we analysed electronic medical records for all adults presenting with LBP at three Australian EDs from January 2016 to June 2018. Outcomes included discharge diagnoses and key aspects of care (ambulance transport, lumbar spine imaging, provision of opioids, admission). We explored factors associated with these care outcomes using multilevel mixed-effects logistic regression models and reported data as ORs. Results: There were 14 024 presentations with a 'visit reason' for low back pain, of which 6393 (45.6%) had a diagnosis of a lumbar spine condition. Of these, 31.4% arrived by ambulance, 23.6% received lumbar imaging, 69.6% received opioids and 17.6% were admitted to hospital. Older patients (OR 1.79, 95% CI 1.56 to 2.04) were more likely to be imaged. Opioids were less used during working hours (OR 0.81, 95% CI 0.67 to 0.98) and in patients with non-serious LBP compared with patients with serious spinal pathology (OR 1.65, 95% CI 1.07 to 2.55). Hospital admission was more likely to occur during working hours (OR 1.74, 95% CI 1.48 to 2.05) and for those who arrived by ambulance (OR 2.98, 95% CI 2.53 to 3.51). Conclusion: Many ED presentations of LBP were not due to a lumbar spine condition. Of those that were, we noted relatively high rates of lumbar imaging, opioid use and hospital admission.